Quantifying the indices of biodiversity and distribution of woody true mangroves in Northern coast of Vietnam - Tinh, Pham Hong; Tuan, Mai Sy (Academia Journal of Biology, 2016)
The method of quantification of species diversity and distribution by the Shannon- Wiener Index (H’), Index of Similarity (SI), Importance Value Index (IVI), Niche width (bi), Complexity Index (CI), Spatial Distribution (Abundance/ Frequency - A/F) was used to quantify the diversity and distribution of woody true mangroves in Dong Rui, Xuan Thuy national park and Hau Loc along northern coast of Vietnam. The results showed that the species diversity and the structural complexity of the woody true mangrove vegetation at the study sites are relatively low, descending from Dong Rui (H = 1.13; CI = 12.15) to Xuan Thuy National Park (H = 0.62; CI = 11.33) and Hau Loc (H = 0.35; CI = 25.54). However the woody mangrove species compositions of the study sites are not highly different (SI ≥ 0.8). The study results also showed that B. gymnorrhiza, A. corniculatum, R. stylosa, A. marina and K. obovata are dominant species in Dong Rui (IVI = 44.36-76.50); K. obovata and A. corniculatum dominate in Xuan Thuy National Park (IVI = 115.20-148.12); K. obovata is the highly dominant species in Hau Loc (IVI = 222.92). Spatial distribution of almost studied species is continuous (A/F > 0.05) indicating the habitat of the species in the study sites is relatively stable.